Analisis Kinerja Keuangan Dengan Time Series Pada Perusahaan Pulp Dan Kertas Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2020 - Magdalena, Firensia; Ratih, Suklimah (Rifa'Institute, 2022)
Financial performance in general is a business carried out by every companies to measure and judge every success achieved in make a profit. One of the measuring tools to determine the financial position and position The success of a company is with the financial ratio. This research aimed to knowing financial performance with a Time Series on Pulp and paper Company Registered Paper Exchange 2018-2020